KfW/ZEW CO2 Barometer 2015 – Manufacturing Industry Edition: Impacts of the energy transition - Karl Ludwig Brockmann; Caroline Dieckhöner; Kerstin Kiehl; Carlo Gallier; Peter Heindl; Daniel Osberghaus (KfW Bankengruppe und Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
Developed as part of a cooperative project of KfW Bankengruppe and the Centre for European Economic Research (ZEW), the KfW/ZEW CO2 Barometer has been analysing the situation of German companies regulated under the European Union Emissions Trading Scheme (EU ETS) on an annual basis since 2009. The study's objective is to closely monitor firm behaviour in carbon markets in order to regularly provide detailed information to policymakers, businesses and the research community. In the framework of the KfW/ZEW CO2 Barometer, KfW Bankengruppe and the ZEW have developed a second annual survey as a complementary study that started two years ago: the KfW/ZEW CO2 Barometer – Manufacturing Industry Edition. The aim is to shed light on recent developments in the German manufacturing industry that are driven by European climate and energy regulations and the German energy transition in particular. The study is based on a survey among German manufacturing firms. The results are presented in this report which is published subsequent to the KfW/ZEW CO2 Barometer – Carbon Edition. The survey questions in the present version address energy price expectations, investment in energy efficiency and the companies' opinion on the German energy transition...
Keywords: 330; CO2 Barometer; Manufacturing; Energy Transition; Germany